Physical Growth of Children with Ventricular Septal Defect - Bambang Madiyono; Eva Jeumpa Soelaeman; Ismet N. Oesman; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 1994)
We conducted a prospective study on children with ventricular septal defect (VSD) for assessing the physical growth status, establishing the determinants of growth, and determining the effect of natural history on growth. There were 46 VSD patients and 30 controls aged 1-5 years. We divided the subjects into two groups; group A consisted of 32 VSD patients and 16 controls aged 12-35 months, group 8 comprised 14 VSD patients and 14 controls aged of 36-60 months. A simple hemodynamic scoring system was created to determine the correlation between physical growth and severity of hemodynamic alteration, using 10 findings based on history, physical, and non-invasive examinations. Body weight and height, and arm circumference were measured every 3 months up to 12 months. The growth status correlated well with the hemodynamic scores. Body weight and arm circumference were more affected than body height Physical growth disturbance was observed in high score patients at the beginning, and became more evident at the end, of the study. In low score patients and circumference was slightly affected at the beginning of the study, while body weight was slightly disturbed after 9 months of observation.